¿Abstract or concrete constitutional judicial review? - Rodríguez Grez, Pablo (Derecho Público Iberoamericano, 2013)
The purpose of article is to precise the power of the Constitutional Court in reviewing the as-applied action of unconstitutionality (recurso de inaplicabilidad) in judicial review of statutory rules. If the Court resolves the cases using an abstract review (only comparing the legal statutory rule with the constitutional norms), then its powers would be reduced. On the contrary, if the judicial review action is considered as a concrete (as applied) examination, the Court’s powers would be increased in a way that the same legal rule can be considered as adjusting the Constitution in some cases, and contradicting constitutional norms in others, depending on judicial interpretation. Since this question must be addressed in the preliminary admissibility examination, and that the concrete review model gives the Constitutional Court powers that belong to non-constitutional ordinary judges, it must be concluded that constitutional justices should only review the statutory rules using an abstract examination.